MODELLING AND SIMULATION OF DYNAMIC PROCESSES OF PNEUMATIC LINES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The paper presents the simulation of dynamic processes of pneumatic lines using the program "SIMULINK" from the product " MatLab". Simulation is a process of forming, preparing and entering a mathematical model in a computational environment and obtaining the results of the calculations performed in this environment. The mathematical model of the pneumatic line to be simulated is according to previously presented equations. For the simulation of the dynamic processes, various real parameters of the dimensions and lengths of the pneumatic lines with the corresponding coefficients are introduced into the model. The simulation of the transient responses was carried out with stepwise variation and sinusoidal input signal supplied by the set point device and pneumatic line lengths of 1 m, 5 m and 10 m. The simulation output data were output to the interface in the form of graphs showing the dependence of the observed quantities, the input and output pressure through the pneumatic line, and the input and output flow rates. From the mathematical model and the experiments performed, it can be concluded that the transient responses in the simulations correspond to the dynamic processes of pneumatic lines of different lengths.